Cyberbullying - Wright, Michelle F. (Victimology, 2022)
Cyberbullying has become a major focus of not only youths, educators, and researchers, but also among the general population, due to high profile cases of cyberbullying victimization involving suicide and the increasing prevalence of these behaviors. The purpose of this chapter is to examine cyberbullying among children and adolescents, referred to as “youths” throughout the chapter. An extension of traditional bullying, cyberbullying is a form of bullying which takes place by means of electronic technologies, such as email, instant messaging, social networking websites, and text messaging through mobile devices. Drawing on research from a variety of disciplines, such as psychology, education, social work, sociology, and computer science, this chapter describes the definition of cyberbullying, the electronic technologies used, the prevalence rates, characteristics and risk factors, negative psychosocial and academic difficulties, theoretical frameworks, recommendations, and future directions.